Getting Down to Business : Strengthening Economies through Business Registration Reforms - Saltane, Valentina; Pan, Jiawen (International Finance Corporation, Washington, DC, 2014)
Business registration remains a complicated and costly process in many countries, hampering entrepreneurial activity and the creation of formal employment. In Bolivia and Uganda, for example, entrepreneurs need to complete 15 procedures to incorporate a limited liability company. In the Gambia and Djibouti, the cost of incorporation is about 180 percent of per capita income, and the average time needed to start up a business in São Paulo, Brazil, is more than 100 days. Rampant bureaucracy and systemic inefficiencies should not pose obstacles for business development and growth. Several research studies find that simpler business start-up processes are associated with higher rates of formal entrepreneurship, lesser development of shadow economies, increased tax revenues, and decreased corruption. It is clear that easy and straightforward business incorporation practices have multiple spillover benefits for the entire economy.